Molecular identification and antimicrobial potential of endophytic fungi against some grapevine pathogens. - Lava H Nashat; Raed A Haleem; Shayma H Ali (PLoS ONE)
Endophytic fungi are microorganisms that, exhibiting within the plant tissues without causing any apparent harm to the host, establish a symbiotic relationship with plants. Host plants provide endophytic fungi with essential nutrients and a protected environment. In exchange, the fungi can enhance the plant's ability to acquire nutrients. They can also play a crucial role in increasing the host plant's tolerance to various abiotic and biotic stresses. Endophytic fungi can produce a wide range of bioactive compounds, some similar to those found in the host plant. In Iraq's Duhok province of the Kurdistan region, the plant species Vitis vinifera has been explored as a habitat for diverse endophytic microorganisms across various ecological environments. During the period from 2021 to 2022, a total of 600 samples were collected from four distinct locations: Bagera, Besfke, Barebhar, and Atrush. From these samples, twelve endophytic fungal species were isolated, including Aspergillus flavipes, Botryosphaeria dothidea, Fusarium oxysporum, Fusarium ruscicol, Fusarium venenatum, Chaetomium globosum, Clonostachys rosea, Mucor racemosus, Penicillium glabrum, Aspergillus terreus, Aspergillus nidulans, and Aspergillus niger, Alternaria alternata, Paecilomyces maximus, Curvularia buchloes. These fungi were introduced for their potential as biocontrol agents against grapevine trunk diseases and grape rotting fungi, which pose significant risks to grapevine health and productivity. Penicilium radiatolobatum, Botrysphaeria dothidea, Fusarium ruscicola, Fusarium venenatum, and Paecilomyces maximus represented the first record as endophytes on grapevine in Iraq. Based on ITS and SSU sequencing, molecular identification confirmed these fungi's presence with sequence identities ranging from 99% to 100%. Phylogenetic analysis revealed that these endophytes could be categorized into five main clusters (A, B, C, D, and E), showing high intra-group similarity. Utilizing the Dual Culture method, the endophyte Paecilomyces maximus demonstrated a 70.83% inhibition rate against Ilyonectria destructans. In the Food Poisoning method, A. flavipes and P. maximus emerged as the most effective inhibitors of Ilyonectria destructans, whereas A. terreus, M. racemosus, and P. maximus achieved complete inhibition (100%) of Botrytis cinerea. Additionally, M. racemosus was identified as the most effective biocontrol agent against Neoscytalidium dimidiatum. In conclusion, the study emphasizes the potential of endophytic fungi from Vitis vinifera as effective biocontrol agents against grapevine diseases, highlighting their role in sustainable vineyard management. These findings lead to further exploration and implementation of these fungi-inserted pest management strategies.